Magnetic Nanoparticles Coated with Anacardic Acid Derived from Cashew Nut Shell Liquid - Casagrande-Denardin, J (2013)
Magnetic nanoparticles functionalized with biomolecules have received special attention due to their various biomedical applications, such as drug delivery and magnetic hyperthermia treatment for cancer. In this study, we present the synthesis and characterization of new nanoparticles coated with anacardic acid derived from cashew nut shell liquid. The results showed that Fe3O4 nanoparticles coated with anacardic acid (AA-MAG) have superparamagnetic behavior and the magnetization is almost equal when compared with the pure Fe3O4. This coating provides stability by preventing the aggregation nanoparticles without losing its magnetization potential. The AA-MAG demonstrates excellent and fast magneto-temperature response which can be used as high-performance hyperthermia agents. © 2013 Springer Science+Business Media New York.